The science of murder : the forensics of Agatha Christie - Valentine, Carla (Sourcebooks, 2022)
"Written by mortician and forensic expert Carla Valentine, The Science of Murder explores the real-life cases that inspired Agatha Christie and shows how the great mystery writer may have kept up to date with the latest developments in forensic science, from ballistics to blood-splatter analysis. Valentine examines the use of fingerprints, firearms, handwriting, impressions, and toxicology in Christie's novels, before finally revealing the role the dead body itself played in offering vital clues to dastardly crimes"-- Provided by publisher.